COMPETENCY MAPPING PER COMPANIES FUNCTIONAL MANAGERIAL IN EAST JAVA - Elsye Tandelilin (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
The rapid changes in business environment required the development in managerial competencies too. In dynamic environment, changes in patterns of works, strategic, and operational decision making in managerial positions require high competence qualifications, which must be possessed by managerial officials. One of the HR competencies – human capabilities – compresses 4 (four) elements, namely knowledge, abilities, skills, and attitudes. Each of the four elements is exposed to three types of levels: ultimate, standard, and supported and this research focus on the ultimate level. The purpose of this study was to describe the map of competencies in four managerial positions as financial manager, human resource manager, marketing manager, and production manager. This research applied a quantitative approach Survey and interview used to collect primary data sources. Non-probability sampling with quota sampling technique is used to collect data with the total of 234 respondents. The results showed that each manager in each position required different competencies to do his/her job effectively.